Zhuang Brocade for Development and Its Implementation to Enable the Future Viability in Southwest China - Xue Yan; Somchai Seviset; Thanate Piromgarn (Revista de Gestão Social e Ambiental, 2024)
Purpose: 1.To study the factors affecting the development decline of Guangxi Zhuang Brocade. 2.Put forward the methods of sustainable development of Zhuang brocade to the problems existing in its development. Theoretical reference: The methods of sustainable development of Zhuang brocade are studied through folk art, design, and project implementation. Method: After comparative analysis, this paper combined with the market and future of Zhuang brocade puts forward four design methods that can help Zhuang brocade. They upgrade the development of Zhuang brocade from four aspects: product design, process production, publicity and sales, and market expansion. Results and Conclusion: This paper puts forward eight ways which can bring positive influence on the sustainable development of Zhuang brocade. Conclusions are drawn from multi-dimensional research and practical projects, and the possibility of future sustainable development of Zhuang Brocade is discussed. Implications of the research: Find out the sustainable development method of Zhuang brocade through research. Enhance the public's awareness of Zhuang brocade, so that Zhuang brocade can be better inherited and developed and is more suitable for modern people's life. Value: Combined with the market and future of Zhuang brocade, this paper puts forward four design methods that can help Zhuang brocade. This research has a guiding effect on the development of Zhuang brocade and puts forward very referential opinions for the sustainable development of Zhuang brocade.
Keywords: Forest, Soil, and Plant Ecology in China; China's Ethnic Minorities and Relations; China's Socioeconomic Reforms and Governance